Comportamiento ecológico y cultura ambiental, fomentada mediante la educación virtual en estudiantes de Lima-Perú: Ecological behavior and environmental culture, promoted through virtual education in students from Lima-Peru - Yangali Vicente, Judith Soledad; Vásquez Tomás, Melba Rita; Huaita Acha, Delsi Mariela; Baldeón De La Cruz, Maruja Dionisia (Revista de Ciencias Sociales, 2021)
The awareness of the population with the environmental problem worldwide, guides the execution of conservation and preservation actions by the actors that make life in the different human and social spaces. The objective of the study was to analyze the implementation of the environmental culture program in strengthening the ecological behavior of students of regular basic education. The intervention was structured around three fundamental axes: solid waste treatment and recycling culture, increasing living spaces, saving water and energy. The study is part of a qualitative approach to action research design, it was used as a technique and instrument: The observation and the semi-structured interview to the students of basic education in Lima, Peru. The results indicate that it has been possible to strengthen its ecological behavior, from the execution of actions in the aforementioned fundamental axes, as part of the environmental culture program. It is concluded that the students before the program showed little concern for the environmental problems of their school and locality. The study allowed the student to reflect, generating a commitment to continue participating with the family in activities in favor of the environment.